Analysis of an Architecture for Measurement of Audience in IPTV Environments - Soares, Eduardo R.; Barrére, Eduardo (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2017)
This work presents the analysis of a software architecture for the measurement of audience and interactivity in IPTV (Internet Protocol TV) environments. The implementation used is in accordance with the recommendations of the ITU (International Telecommunication Union), taking into account its mandatory requirements. We analyzed factors that may interfere with the architecture performance and may generate the need to treat aspects related to the scalability of the solution. Load tests were performed through stochastic models that simulate the interaction of users with the IPTV environment. Thus, besides presenting the viability of the implementation, the aspects that must be taken into account for the implementation of an IPTV audience measurement architecture in a real environment are analyzed.